Alternate row placement is ineffective for cultural control of Meloidogyne incognita in cotton - Davis, Richard F (Journal of nematology, 2008)
The objective of this study was to determine if planting cotton into the space between the previous year's rows reduces crop loss due to Meloidogyne incognita compared to planting in the same row every year. Row placement had a significant (P </= 0.05) effect on nematode population levels only on 8 July 2005. Plots receiving 1,3-dichloropropene plus aldicarb had lower nematode population levels than non-fumigated plots on 24 May and 8 July in 2005, but not in 2004. The effect of nematicide treatment on nematode populations was not affected by row placement. Row placement did not have a significant effect on root galling or yield in 2004 or 2005. Nematicide treatment decreased root galling in all years, and the decrease was not influenced by row placement. Yield was increased by nematicide application in 2004 and 2005, and the increase was not affected by row placement. Percentage yield loss was not affected by row placement. Changing the placement of rows reduced nematode population levels only on one sampling date in one year, but end-of-season root galling and lint yield were not affected by changing the placement of rows, nor was the effect of fumigation on yield influenced by row placement. Therefore, row placement is unlikely to contribute to M. incognita management in cotton